Firmy medyczne na rynku zamówień publicznych samodzielnych publicznych zakładów opieki zdrowotnej - Lewandowska, Hanna (Medical Companies on the Market of Independent Public Health Centre, 2006)
Activities of health centres (independent public health centres) and medical companies are correlated with each other despite the different range and different purposes of their existence. Direction of undertaken activities and processes of changes in health sector are dependent upon efficiency of operation of the medical companies. Market of public orders, on which, as a result of a market play, costs and incomes of the market are created, constitutes one of the areas ability to verify the optimal directions of the undertaken activities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 111-119